Caracterización de la morbilidad oral del adulto mayor. parroquia Guanando, 2019 - Jennifer Katherine, Mosquera Sánchez (2019)
Through the years, the geriatric population has formed a population group at risk, either by their oral manifestations of systemic, which in one way or another condition their quality of life. Diseases such as dental caries, periodontal disease, edentulous are some of the most chronic oral conditions in older adults. This research was developed to characterize the oral morbidity of the elderly of the parish of Guanando, 2019. Using a descriptive cross-sectional study, with a population made up of a non- probabilistic way where the subjects of studies met the selection criteria and were of both sexes. Concerning the sample was composed of 64 medical records obtained from the databases of links with society, they collected by students of Dentistry of the UNACH. The sample processed in SPSS v.25. As a result, it determined that the oral pathologies present in the elderly are: Geographic tongue (18.8%), 18.8%) macroglossia (pathologies present in women; however, the angular cheilitis (23.4%) was exclusive to men of that population. It concluded that although the oral pathologies do not obey to a pattern of a certain age, there are diseases that tend to be more common in older adults, due to the little care of their habits of hygiene, there were no significant differences found between age and the categories of morbidities (p=0,465).